Desain strategi rekonstruksi dalam penulisan cerita rakyat untuk penguatan literasi kearifan lokal santri pondok pesantren - Susiati, Susiati; Pratiwi, Yuni (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
One form of immaterial wealth that is very valuable of community in Trenggalek district area is folklore. Folklore contains information about traditional knowledge systems, attitudes, and behaviors, some of which are still very relevant to life today. The purpose of this study is to analyze the needs of learning strategy design to improve students' understanding of reading content in boarding school-based schools. This research is a research and development with the 4D model carried out up to the define and design stages to produce a story reconstruction strategy design. The subjects of this study consisted of 40 students and teachers assisting literacy activities at MTs Satu Atap Darunnajah. This research focuses on (1) the design of folklore reconstruction strategies, (2) the potential of folklore as a learning resource, and (3) the content of local wisdom in accordance with Islamic teachings. The result of this research is a folklore reconstruction strategy design that includes five stages, namely reading, telling stories, reflecting on the values in the story, linking the results of reflection with hadith or Al-Qur'an verses, and writing new stories. The reconstruction strategy design developed can be used to optimize literacy activities in boarding school-based schools.